The effect of hydrostatic pressure on model membrane domain composition and lateral compressibility - Barriga,HMG; Law,RV; Seddon,JM; Ces,O; Brooks,NJ (Physical Chemistry Chemical Physics, 2015)
Phase separation in ternary model membranes is known to occur over a range of temperatures and compositions and can be induced by increasing hydrostatic pressure. We have used small angle X-ray scattering (SAXS) to study phase separation along pre-determined tie lines in dioleoylphosphatidylcholine (DOPC), dipalmitoylphosphatidylcholine (DPPC) and cholesterol (CHOL) mixtures. We can unequivocally distinguish the liquid ordered (Lo) and liquid disordered (Ld) phases in diffraction patterns from biphasic mixtures and compare their lateral compressibility. The variation of tie line endpoints with increasing hydrostatic pressure was determined, at atmospheric pressure and up to 100 MPa. We find an extension and shift of the tie lines towards the DOPC rich region of the phase diagram at increased pressure, this behaviour differs slightly from that reported for decreasing temperature.